2006
DOI: 10.1007/s11129-006-9010-4
|View full text |Cite
|
Sign up to set email alerts
|

The shipping strategies of internet retailers: Evidence from internet book retailing

Abstract: Managing the shipment of goods to consumers is one of the central aspects of retail competition on the internet. In this article, we analyze internet retailers’ shipping strategies using data from the internet book retailing industry. We find that, controlling for a variety of observable firm characteristics, firms with lower product prices offer lower shipping fees and higher quality shipping in terms of average delivery time, compared to firms with higher product prices. These patterns cannot be readily reco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
1
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 22 publications
3
25
1
1
Order By: Relevance
“…It is the total of the item's price and shipping cost. Earlier research has suggested that Internet retailers manipulate products' price and shipping charges to gain a competitive advantage (Dinlersoz and Li 2006). Measuring total cost (i.e., a product's price and shipping charges), as done by Brynjolfsson and Smith (2000) and Pan et al (2002Pan et al ( , 2003a, can eliminate potential price dispersion resulting from such manipulation.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…It is the total of the item's price and shipping cost. Earlier research has suggested that Internet retailers manipulate products' price and shipping charges to gain a competitive advantage (Dinlersoz and Li 2006). Measuring total cost (i.e., a product's price and shipping charges), as done by Brynjolfsson and Smith (2000) and Pan et al (2002Pan et al ( , 2003a, can eliminate potential price dispersion resulting from such manipulation.…”
Section: Descriptive Analysismentioning
confidence: 99%
“…Second, Raya may view bidding and shipping as different attributes of the auction item, or even as two separate pieces of information (Dinlersoz and Li, 2006). When integrating multiple information pieces into an overall judgment consumers oftentimes use a heuristic approach, termed as anchoring and adjustment (Tversky and Kahneman, 1974;Yadav, 1994).…”
Section: Shipping Chargesmentioning
confidence: 99%
“…Most relevant to mail/ web retailing, Dinlersoz and Li (2006) report that internet booksellers almost all use uniform pricing. Less relevant due to focus on industrial markets are two papers: Phlips (1983) presents examples of uniform pricing in Europe in the cement and plasterboard industries, and Greenhut (1981) shows that in industrial markets uniform pricing is widely used.…”
Section: Literature Reviewmentioning
confidence: 99%